2013
DOI: 10.1007/s11356-013-2163-2
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Cd-, Pb-, Zn-resistant endophytic Lasiodiplodia sp. MXSF31 from metal accumulating Portulaca oleracea and its potential in promoting the growth of rape in metal-contaminated soils

Abstract: The aim of this study was to characterize the features of a Cd-, Pb-, and Zn-resistant endophytic fungus Lasiodiplodia sp. MXSF31 and to investigate the potential of MXSF31 to remove metals from contaminated water and soils. The endophytic fungus was isolated from the stem of Portulaca oleracea growing in metal-contaminated soils. The maximum biosorption capacities of MXSF31 were 3.0 × 10(3), 1.1 × 10(4), and 1.3 × 10(4) mg kg(-1) for Cd, Pb, and Zn, respectively. The biosorption processes of Cd, Pb, and Zn by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(37 citation statements)
references
References 35 publications
0
37
0
Order By: Relevance
“…Most studies have been undertaken on filamentous fungal strains and mostly members from the genera Aspergillus, Fusarium, Humicola and Nannizzia have been reported to possess resistance against heavy metals (Iram et al 2013;Ezzouhri et al 2009;Valix et al 2001). Recently, several studies have reported a similar trend among endophytic fungi being able to resist several heavy metals such as copper, zinc and cadmium (Hong et al 2010;Salvadori et al 2013;Deng et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Most studies have been undertaken on filamentous fungal strains and mostly members from the genera Aspergillus, Fusarium, Humicola and Nannizzia have been reported to possess resistance against heavy metals (Iram et al 2013;Ezzouhri et al 2009;Valix et al 2001). Recently, several studies have reported a similar trend among endophytic fungi being able to resist several heavy metals such as copper, zinc and cadmium (Hong et al 2010;Salvadori et al 2013;Deng et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…This was consistent with previous research that presoaking the seeds can alleviate the adverse effect caused by salinity stress during germination (Ashraf and Foolad 2005). As a current hot research topic, in the assessment of the phytoremediation of Cd (Cocozza et al 2014;Deng et al 2014;Luo et al 2014;Moreira et al 2014), cadmium affected higher plant seed germination and seedling growth mainly in the following ways: inhibiting the activity of some carbohydrate-hydrolyzing enzymes in seed (Kuriakose and Prasad 2008), suppressing the elongation growth rate of root and stem cells (Munzuroglu and Geckil 2002), and strongly inhibiting the synthesis, construction, and activity of some key enzymes key in metabolic processes (Das et al 1997). Previous studies have indicated that seed germination and seedling growth response to Cd stress largely depends on different plant species and varieties as well as Cd concentrations to some extent (An 2004;Das et al 1997;Wang and Zhou 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Among all of the heavy metals, cadmium, in particular, is an extremely dangerous pollutant that requires special concern due to its relatively high mobility in soils and water and its high toxicity to plants, animals, and humans, even at very low concentrations (Benavides et al 2005;Deng et al 2014;Storelli 2014;Xiao et al 2013). It is often released into the environment by power stations, heating systems, metalworking industries, and mining.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies have been undertaken on filamentous fungal strains and mostly members from the genera Aspergillus, Fusarium, Humicola, and Nannizzia have been reported to possess resistance against heavy metals [13,23,25]. Recently, several studies have reported a similar trend among endophytic fungi being able to resist several heavy metals such as copper, zinc, and cadmium [26][27][28]. The preliminary screening of endophytic fungi against heavy metals showed the order of tolerance to heavy metals are Cd<Cu<Zn<Co.…”
Section: Screening Of Fungal Isolates Against Heavy Metalsmentioning
confidence: 99%